Expanding the phenotype of DNAJC30‐associated Leigh syndrome. Issue 5 (29th July 2022) - Zawadzka, Marta; Krygier, Magdalena; Pawłowicz, Małgorzata; Wilke, Matheus Vernet Machado Bressan; Rutkowska, Karolina; Gueguen, Naig; Desquiret‐Dumas, Valerie; Klee, Eric W.; Schimmenti, Lisa A.; Sławek, Jarosław; Procaccio, Vincent; Płoski, Rafał; et al.
Abstract: Leigh syndrome (LS) is a progressive neurodegenerative disease, characterized by extensive clinical, biochemical, and genetic heterogeneity. Recently, biallelic variants in DNAJC30 gene, encoding a protein crucial for the repair of mitochondrial complex I subunits, have been associated with Leber hereditary optic neuropathy and LS. It was suggested that clinical heterogeneity of DNAJC30 ‐associated mitochondrial disease may be attributed to digenic inheritance. We describe three Polish patients, a 9‐year‐old boy, and female and male siblings, aged 17 and 11 years, with clinical and biochemical manifestations of LS. Exome sequencing (ES) identified a homozygous pathogenic variant in DNAJC30 c.152A>G, p.(Tyr51Cys) in the 9‐year‐old boy. In the siblings, ES identified two DNAJC30 variants: c.152A>G, p.(Tyr51Cys) and c.130_131del, p.(Ser44ValfsTer8) in a compound heterozygous state. In addition, both siblings carried a novel heterozygous c.484G>T, p.(Val162Leu) variant in NDUFS8 gene. This report provides further evidence for the association of DNAJC30 variants with LS. DNAJC30 ‐associated LS is characterized by variable age at onset, movement disorder phenotype and normal or moderately elevated blood lactate level. Identification of a candidate heterozygous variant in NDUFS8 supports the hypothesis of digenic inheritance. Importantly, DNAJC30 pathogenic variants should be suspected in patients with LS irrespective of optic nerve involvement. Abstract : Three patients, each harboring biallelic DNAJC30 missense and frameshift variants underwent extensive clinical, biochemical, and molecular investigations. DNAJC30 ‐associated disease has a variable clinical presentation, ranging from movement disorder to isolated optic atrophy. Identification of a candidate heterozygous variant in NDUFS8 supports the hypothesis of digenic inheritance.